Mental illness as social product or social construct: a contradiction in feminists’ arguments? - Busfield, Joan (Sociology of Health & Illness, 2008)
Feminists have been taken to task for suggesting both that the higher level of mental illness observed in women is a consequence of the oppression they face - an oppression which drives them into madness and mental disorder - and also that the concept of mental illness is a social construct inappropriately and incorrectly applied to women by a patriarchal order as a means of social control. This paper examines this supposed contradiction and the ideas that underly the contrasting contentions. It argues that the two positions are not in fact incompatible.
Number: 4
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; angleterre; approches et analyses; cours; discipline; europe; inégalités; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; santé mentale; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Le droit à l’avortement, une lutte exemplaire - Revue À bâbord ! - bâbord!, Revue À (2008)
Militante de longue date pour le droit à l’avortement, Louise Desmarais publie en 1998 La lutte pour le droit à l’avortement, histoire d’une bataille inachevée. Elle présente ici les principales caractéristiques et les moments forts, selon elle, de la lutte pour le droit à l’avortement au Québec.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amériques; approches et analyses; avortement; canada; care; corps; cours; discipline; histoire; justice reproductive; justice sociale; militance; pol4102; premier cycle; périodes historiques; québec; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail social

Sport et bicatégorisation par sexe : test de féminité et ambiguïtés du discours médical - Bohuon, Anaïs (Nouvelles Questions Féministes, 2008)
Dès les années 30, des sportives font l’objet d’un procès de virilisation dans des épreuves d’athlétisme en raison de morphologies jugées trop « masculines ». Ces athlètes se rapprochent des hommes non seulement par le physique, mais aussi par leurs performances. Des soupçons sont alors émis quant au sexe des sportives. En 1966, un test de féminité est instauré par le monde médical sportif afin de contrôler le sexe des concurrentes et s’assurer que celles-ci ne bénéficient pas d’avantages physiques que les femmes ne sont pas censées posséder. Notre article consiste à montrer les ambiguïtés des discours médicaux face aux controverses soulevées par le test de féminité qui, dévoilant les niveaux pluridimensionnels de l’identité sexuée, obligent le milieu médico-sportif à s’interroger sur la définition d’une « vraie femme ».
Number: 1
Keywords: 1900-1999; 1930-1939; 1960-1969; approches et analyses; cours; discipline; discours dominant; europe; france; postmodernisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2051; sociologie; sport; systèmes d'oppressions; thématiques

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Les femmes et la vie culturelle à Québec avant la Révolution tranquille - Harvey, Fernand (Cap-aux-Diamants : la revue d'histoire du Québec, 2008)
https://id.erudit.org/iderudit/6856ac
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amériques; discipline; histoire; histoire des femmes*; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Firekeepers of the twenty-first century: First Nations women chiefs - Voyageur, Cora Jane (McGill-Queen's University Press, 2008)
A quiet revolution is occurring in Canada's First Nations communities, with changes taking place on social, political, and economic fronts and a significant redistribution of power. Changes to the Indian Act in 1951 paved the way for women to become officially involved in reserve politics, and with governments responding to the demand of First Nations for self-government, positions once held exclusively by men are now being filled by women. Beginning with Elsie Knott, the first female chief in Canada, Cora Voyageur presents the lives of sixty-four of the ninety women chiefs who have assumed the traditionally male role of elected First Nations leadership. Using a range of qualitative research strategies, surveys, participant observation, interviews, and discussions with focus groups, Voyageur presents the colonial histories behind the issues that contemporary Aboriginal communities struggle with and delineates the resulting leadership dilemmas for chiefs, while also articulating a story that is unique to First Nations women. Voyageur asks women chiefs about what inspired them to become leaders, how they've maintained their priorities, and the personal and professional costs and rewards involved in their positions. Firekeepers of the Twenty-First Century is a groundbreaking work that examines the experiences of women as they negotiate multiple roles and navigate the worlds of gender, race, and reserve politics.
Section: xxi, 157 pages
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; entretien; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; féminisme décolonial; gouvernance; histoire et politique; militance; pol4105; pouvoir; premier cycle; premières nations; périodes historiques; régions géographiques; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques